If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4u + -6)(8 + -1u) = 0 Reorder the terms: (-6 + 4u)(8 + -1u) = 0 Multiply (-6 + 4u) * (8 + -1u) (-6(8 + -1u) + 4u * (8 + -1u)) = 0 ((8 * -6 + -1u * -6) + 4u * (8 + -1u)) = 0 ((-48 + 6u) + 4u * (8 + -1u)) = 0 (-48 + 6u + (8 * 4u + -1u * 4u)) = 0 (-48 + 6u + (32u + -4u2)) = 0 Combine like terms: 6u + 32u = 38u (-48 + 38u + -4u2) = 0 Solving -48 + 38u + -4u2 = 0 Solving for variable 'u'. Factor out the Greatest Common Factor (GCF), '2'. 2(-24 + 19u + -2u2) = 0 Factor a trinomial. 2((-8 + u)(3 + -2u)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-8 + u)' equal to zero and attempt to solve: Simplifying -8 + u = 0 Solving -8 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + u = 0 + 8 Combine like terms: -8 + 8 = 0 0 + u = 0 + 8 u = 0 + 8 Combine like terms: 0 + 8 = 8 u = 8 Simplifying u = 8Subproblem 2
Set the factor '(3 + -2u)' equal to zero and attempt to solve: Simplifying 3 + -2u = 0 Solving 3 + -2u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2u = 0 + -3 -2u = 0 + -3 Combine like terms: 0 + -3 = -3 -2u = -3 Divide each side by '-2'. u = 1.5 Simplifying u = 1.5Solution
u = {8, 1.5}
| 2x-1=32 | | 92x=27 | | 7x^2+6x+3=0 | | x+1=-1+-5 | | 5x^2+7+2=0 | | -3b(2a-3b)+6(-6ab+25b)= | | R=y | | -3b(2a-3b)+6(-6ab-25b)= | | 100[0.06(y+2)]= | | 4x+1=5x+(-5) | | -(x-9y)= | | 4x+1=5x+-5 | | 3log(x+2)=6 | | 6n+6=(n+8)-7n | | 1+sqrt(x+5)=sqrt(2x+5) | | (12a^4b-7a^2b^2+8ab^3)+(-6a^4b-5a^2b^2+3ab^3)= | | 2x-4+7=3 | | (x-4)(x-8)=5 | | 10x^2-3x=6x-8x^2 | | 2x-9=-6 | | 2+5(10)= | | (6x^2y-4xy^2)-(-9x^2y-7xy^2)= | | 2x^2-20x-5525=0 | | 100[0.06(n+10)]= | | 2b^3-4=r^8 | | 50x-4=45x+1 | | 2y^6+9=g^1 | | 50x-1=45x+1 | | -1x-6y=5 | | C-16=18 | | B+127=52 | | -x+6y=5 |